Measuring and managing risk in UK listed firms - Roberts, Patrick (2016)
The last twenty years have seen sustained pressure on firms in the UK and globally to demonstrate good corporate governance and, in particular, to manage risk in an appropriate manner; the overall aim of this study is therefore to contribute to the understanding of how to measure and manage risk at the firm level more effectively. This involves three specific research objectives: to investigate the measurement properties of some of the most commonly used corporate risk measures; to investigate the relationship between risk and return at the firm level; and to investigate the drivers for the development of a risk management capability within firms. The research objectives were addressed in the context of UK firms, using accounting data from the FAME database and market data from Datastream. A particular criticism of previous research in these areas is the lack of consideration about how to handle extreme values in the distributions of risk measures; so a number of different techniques, specifically designed to be robust to outliers, are employed throughout this study.